Global risk from trade wars : time to return to WTO - Desker, Barry (2013)
The WTO Doha Round of negotiations is deadlocked and adrift amid increasing global protectionism. The profusion of bilateral and plurilateral free trade agreements is asdding to the confusion. A global solution is necessary for global problems.